Short Communication: First record of the Genus Calamaria (Squamata: Colubridae: Calamariinae) from Karimunjawa Island, Indonesia: Morphology and systematic - IRVAN SIDIK; DADANG R. SUBASLI; SUTIMAN B. SUMITRO; NASHI WIDODO; NIA KURNIAWAN (Society for Indonesian Biodiversity, 2018)
Sidik I, Subasli DR, Sumitro SB, Widodo N, Kurniawan N. 2018. Short Communication: First record of the Genus Calamaria (Squamata: Colubridae: Calamariinae) from Karimunjawa Island, Indonesia: Morphology and systematic. Biodiversitas 19: 912-917. We present the first record of the Genus Calamaria from Karimunjawa Island, Central Java, Indonesia based on an unfathomable single specimen collected in the coastal forest of Legon Moto. Morphological characters analysis revealed the specimen as Calamaria melanota. This finding unravels the extent of the species distribution which was previously thought to be restricted in Borneo, representing the southernmost record of this species. The examined specimen is described in detail and meticulously compared with other Calamaria species such as C. battersbyi, C. borneensis, C. linnaei. Our study highlights several characteristic differences between the specimen and the holotype of C. melanota.